Epidermolysis Bullosa with Pyloric Atresia and Aplasia Cutis in a Newborn Due to Homozygous Mutation in ITGB4. (4th July 2017) - Kayki, Gozdem; Bozkaya, Davut; Ozaltin, Fatih; Orhan, Diclehan; Kaymaz, Figen; Korkmaz, Emine; Yigit, Sule
ABSTRACT: Background : Epidermolysis bullosa with pyloric atresia (EB-PA) is an autosomal recessive disorder due to mutations in ITGA6 and/or ITGB4, resulting in altered expression of α6β4 integrin. EB-PA can also occur with aplasia cutis. Case report : We present a newborn with EB-PA and aplasia cutis, born of consanguineous parents, with a homozygous c.3793+1G>A mutation affecting ITGB4, previously described only in the heterozygous state with other mutations. Conclusion : The previously unreported homozygous c.3793+1G>A mutation affecting ITGB4 causes a severe form of junctional epidermolysis bullosa with pyloric atresia and aplasia cutis.